The razor - Mitchell, J. Barton (Tor, 2018)
"Marcus Flynn has been sentenced to the terrifying prison planet known as the Razor. There's only one problem. He's innocent. He's barely made it through the first day when everything changes: All the guards and prison personnel suddenly abandon the planet, leaving the inmates there to die. There is more to the Razor than meets the eye and Flynn soon finds himself making unlikely allies and the most dangerous of enemies" --